Knowledge, awareness and practice on oral health care among pregnant mother in antenatal clinicl at Hospital Universiti Sains Malaysia - Razali, Nur Asma (2020)
Oral health care involves the care and cleansing of the entire mouth and teeth. The purpose of this study was to evaluate knowledge, awareness and practice of oral health care among pregnant women in antenatal clinics at Hospital USM. Descriptive design of cross-sectional designs was used for this study. A total of 50 pregnant mothers were recruited using a simple random sampling method. The instruments used for this study were a set of questions about demographic data, oral health care knowledge, oral health care awareness and oral health care practices. Scoring according to the correct answer to the knowledge question, "yes" or "no" to the awareness question and three scale creators for practice questions. For each correct answer one score will be given. Data were analyzed in SPSS (version 24) and the results are presented in the table. Most pregnant mothers had good knowledge of oral health care with 83(85%). Meanwhile, 84 (85.8%) pregnant mothers had a good awareness of oral health care. In addition, oral health practices in 43 pregnant mothers (46.7%) were good practices in oral health care. However, 26.1(27%) and 27.2(26.3%) pregnant mother had moderate and weak practices of oral health care, respectively. In conclusion, the findings of the study indicate the need for adequate formal information and appropriate oral health care practices in pregnant women to reduce complications of oral and birth problems in Malaysia.